Families adapting to COVID-19 in urban Bangladesh: “It felt like the sky fell apart and we were in shock” - Nandonik, Ahmed Jojan; Das Pooja, Shangjucta; Kabir, Zarina Nahar; Kiriam, Shoshannah (Frontiers in Psychology, 2024)
The COVID-19 epidemic has especially impacted the urban population in Bangladesh. Studies on COVID-19 have primarily focused on the patient's perspective. It is important to understand the experience of family members who adopt caregiving roles, as the experience of COVID-19 also impacts, and is impacted by, household members. This study aimed to explore the challenges, preventative practices, health-seeking behaviour, and navigating the health care system from the perspective of family members of persons who had recovered from COVID-19 during its initial outbreak in Bangladesh.Methods: Participants of this qualitative study were family members (n=7) of persons who had recovered from COVID-19 (either suspected or confirmed). Semi-structured in-depth interviews were conducted over telephone.Thematic analysis was used to analyse the data.Results: Analysis revealed three key themes: changes in everyday practices and choice of health care, challenges and constraints, and unexpected positive outcomes. All the themes had temporal dimension to them with four distinct phases: early stage of COVID-19, strict lockdown phase, COVID-19 diagnosis and illness period and post COVID-19 recovery.The importance of maintaining social contact for psychological wellbeing during critical times was evident in the study. Online communication and social media enabled participants to remain 'socially connected' which further supported their mental health. Increased attention to hygiene practices both before, during and subsequent to COVID-19 infections within families was reported. Physical distancing in case of a suspected or confirmed COVID-19 case was found logistically and socially impractical in a densely populated city.